SOME LEGAL ISSUES AND THEIR CONSEQUENCES IN THE METAVERSE: IN CASE OF FOUR MAIN CHALLENGES - Mukhammad Ali Turdialiev (Scholar Express Journals, 2023)
In this article analyzed four main legal issues and their consequences in the metaverse world. Moreover it is also illustrated some collision regulatory of relation in metaverse. In addition discussed diversity of scientific views on crypto currency and other private issues in metaverse. As a result of these analyzes suggested some recommendation for the development of legislation on virtual relations.
Keywords: metaverse; crypto coin; crypto currency; NFT